2011
DOI: 10.1021/jp109088h
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ionic Liquid in Confined Media: A Temperature Dependence Solvation Study in [bmim][BF4]/BHDC/Benzene Reverse Micelles

Abstract: In this work, we reported a detailed study of the solvation dynamics of coumarin-480 in [bmim][BF(4)]/BHDC/benzene reverse micelles (RMs) with varying [bmim][BF(4)]/BHDC molar ratio (R) 1.00, 1.25, 1.50, and also study the solvation dynamics at five different temperatures from 15 to 35 °C RMs at [bmim][BF(4)]/BHDC molar ratio 1.25 for the first time. The average solvation time constant becomes slightly faster with the increase in R values at a temperature 25 °C. The solvation dynamics of the RMs with R value 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 89 publications
11
44
0
Order By: Relevance
“…To cover the additional IL, the surfactant aggregates were expanded, resulting in a larger particle diameter of the MEs [8]. In addition, by plotting particle size as a function of R, it was found that the particle size was an almost linear function of R, as shown in Figure S5, and according to the swelling law of MEs, this indicated spherical ME droplets [37]. Moreover, the particle size of the MEs was also studied at constant R values (by varying the surfactant and IL), and it was found that with increasing surfactant content, the number of particles was also increased while keeping a constant particle size ( Figure S6) [8].…”
Section: Particle Size Determinationmentioning
confidence: 97%
See 1 more Smart Citation
“…To cover the additional IL, the surfactant aggregates were expanded, resulting in a larger particle diameter of the MEs [8]. In addition, by plotting particle size as a function of R, it was found that the particle size was an almost linear function of R, as shown in Figure S5, and according to the swelling law of MEs, this indicated spherical ME droplets [37]. Moreover, the particle size of the MEs was also studied at constant R values (by varying the surfactant and IL), and it was found that with increasing surfactant content, the number of particles was also increased while keeping a constant particle size ( Figure S6) [8].…”
Section: Particle Size Determinationmentioning
confidence: 97%
“…Pharmaceutics 2020, 12, 392 9 of 18 spherical ME droplets [37]. Moreover, the particle size of the MEs was also studied at constant R values (by varying the surfactant and IL), and it was found that with increasing surfactant content, the number of particles was also increased while keeping a constant particle size ( Figure S6) [8].…”
Section: Particle Size Determinationmentioning
confidence: 99%
“…15 To date, almost all research on the self-assembly of surfactants in ILs has exclusively focused on using nonionic surfactants, like Triton X-100, Tween 20 and Brij 30. 26 44,45 We noted that the phase behavior of both microemulsions has many features in common with the corresponding aqueous systems. Different from the Triton X-100 system, their microemulsion size falls into the normal range, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…26 Recently, new surfactants such as cationic benzylhexadecyldimethylammonium chloride (BHDC) and anionic [bmim][AOT] have proven highly effective for forming reverse microemulsions with [bmim][BF 4 ] solvent. 44,45 We noted that the phase behavior of both microemulsions has many features in common with the corresponding aqueous systems. Different from the Triton X-100 system, their microemulsion size falls into the normal range, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Uritski and Huppert studied the solvation dynamics of Coumarin-343 and 2-naphthol-6,8-disulfonate in methanol doped ice and in cold liquid ethanol varying the temperature from 160-270 K. 18 The solvation dynamics in the ionic liquids containing microemulsions was reported. 13,[19][20][21][22] The photophysics of 7-(N,N 0 -diethylamino)coumarin-3-carboxylic acid (7-DCCA) (Scheme 1) is relatively unknown and very few studies are reported in the literature. Ramakrishna and Ghosh studied the photophysical properties of 7-DCCA and Coumarin-343, by adsorbing them on the TiO 2 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%